Pengaruh Penambahan Tepung Rumput Laut (Cottonii, Spinosum, Gracilaria) Terhadap Kandungan Nutrisi (Protein, Dan Kadar Abu) Amplang Ikan Tongkol - Esri Ruga Tumaya; Tjodi Harlim; Lyse Bulo (Paulus Chem Engineering Journal, 2022)
The technology of diversifying the processing of komo tuna fish pulp, which is nutritious and rich in fiber, is carried out by adding cottonii, Spinosum, and Gracilaria types of seaweed flour. In this paper, we will discuss the effect of adding cottonii, Spinosum, Gracilaria seaweed flour to the nutritional content (protein, and ash content) of komo tuna (Euthynnus affinis) amplang, and the panelists' preference for komo tuna (Euthynnus affinis) amplang. seaweed flour (cottonii, spinosum, gracilaria) was added through hedonic test. The method used is an experiment with the main stages covering the preparation of raw materials, making seaweed flour, making komo tuna fish amplang. The results obtained were the addition of seaweed flour (cottonii, spinosum, gracilaria) had an effect on the protein content and ash content of amplang komo tuna (Euthynnus affinis). The protein content of tuna Amplang is 25.9% for the addition of Cottonii type seaweed, while the ash content does not meet the SNI standard for the addition of seaweed to Amplang. Amplang organoleptic test obtained the highest number of appearances in the treatment without the addition of seaweed flour, then followed by cottonii, spinosum and finally gracilaria seaweeds, as well as the high textural values in the treatment without the addition of seaweed flour.